Gas chromatographic determination of styrene and other volatile organic compounds in polystyrene food packaging - Lu, Susie Ling (2008)
Testing of food packaging materials with reliable method gives consumers the assurance to the safety of the products. In this study, material and migration tests of styrene and other volatile organic compounds (VOCs) (toluene, ethylbenzene, iso-propylbenzene and n-propylbenzene) for polystyrene food packaging, using gas chromatography-flame ionization detection (GC-FID) are presented. In the material test, dissolution technique using dichloromethane was used to extract the analytes from the samples. The developed method was validated for specificity, detection limits, linearity, precision and accuracy. The applicability of the method to determine the targeted analytes in a number of commercial polystyrene food packaging was demonstrated. The results show that the dissolution technique with direct injection using GC-FID is effective for simultaneous analysis of five analytes in polystyrene food packaging. This direct injection method with limit of quantification (LOQ) of 8 mg/kg was lacking in sensitivity for migration study. Hence, headspace-solid phase microextraction (HS-SPME) technique was applied for migration test using water as food simulant. The effects of extraction variables including sample volume, elutropic strength, extraction temperature, extraction time, desorption time, sample agitation, and salt addition on the amounts of the extracted analytes were studied and optimal conditions were obtained for HS-SPME extraction. The method was validated, and the LOQ obtained at ppb and sub-ppb level was sensitive enough to detect the VOCs in the migration test. The optimized method was applied to test the analytes migration from polystyrene bowls and cups at storage temperatures ranging from 24°C to 80°C for 30 min. Styrene and ethylbenzene were observed to migrate from the samples into the food simulant. The migration of analyte was found to be strongly dependent upon the storage temperature. The maximum observed migration was from the polystyrene cup at simulating condition of 80°C for 30 min. The HS-SPME is useful as an alternative method to determine the migration of VOCs from food packaging material into food simulant.